Using Image-guided Intensity-modulated Radiotherapy on Patients With Head and Neck Soft-tissue Sarcoma - ELSAYAD, KHALED (In Vivo, 2019)
Background: Image-guided intensity-modulated radiotherapy (IG-IMRT) is increasingly being used to treat patients with soft-tissue sarcoma (STS) of the head and neck. Although there is no comparison between IMRT and conventional radiation therapy (CRT) concerning their efficacy. In this analysis, we compared CRT and IMRT outcomes for head and neck STS. Patients and Methods: Sixty-seven patients who underwent radiotherapy between 1994 and 2017 were identified. Results: The median follow-up was 31 months. Of the 67 patients, 34% were treated with CRT technique and 66% with IG-IMRT. The locoregional relapse rate following IMRT was 21% versus 70% with CRT (p<0.001) and the 5-year locoregional control was 69% versus 28%, respectively (p=0.01). IG-IMRT was associated with non-significant, less acute, and chronic adverse events. In the multivariate analysis, a significant influence of radiation technique on locoregional control was confirmed (p=0.04). Conclusion: IG-IMRT seems to be associated both with higher locoregional control as well as lower acute and chronic toxicities.